The Presupposition Usage in Disney Zombies 2: Pragmatic Study - Samuel Samuel; Ervina CM Simatupang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research aims to find the presupposition types and analyze the purpose of speaker's utterances found in Disney Zombies 2. Presupposition is something assumed or presupposed to be true in a sentence or utterance which asserts other information. Based on Yule (1996: 28) presupposition is classified by six types, namely existential, factive, lexical, structural, non-factive, and counterfactual. Qualitative method was used by the writer in analyzing the data. Then, the data were taken from every character’s utterance which contains presupposition in Disney Zombie 2. From the results of the analysis, it was discovered all types of presupposition and the most dominant presupposition type is used by the characters was existential presupposition includes 4 utterances of existential (33%), 2 utterances of factive (17%), 1 utterance of lexical (8%), 2 utterances of structural (17%), 1 utterance of non-factive (8%), and 2 utterances of counterfactual presupposition (17%). Then, the speaker purposed that he/she wants to tell the listener the information which becomes exist and to be true (Existential), to show the listener the information which is conveyed is a fact (Factive), to convey the unstated meaning to the listener (Lexical), to know the truth of the missing information (Structural), to show the falsity condition of a case (Non-Factive), to show the opposite from the actual condition (counterfactual).